"Eco-aldea turística sostenible y sustentable para la comunidad reserva cañón del Magdalena (San Agustín, Huila) " (2021)
The Magdalena River is one of the most important rivers in Colombia, however, currently in the area where it is born, deforestation and partial burning of certain areas of the canyon have been evidenced, where it begins to form in the perimeter areas of the source of the tributary which puts at risk the ecosystem and the original conditions that make the Magdalena River begin to generate a greater flow. If these natural conditions are affected by the phenomena described in the previous paragraph, this would cause the Magdalena Lagoon to begin to reduce its water level and cause negative effects on water generation, where the source of the river originates, generating damage totally irreparable in the ecosystem, which would affect not only the current population, but also future generations. Therefore, in this area specifically is where the Magdalena River is most vulnerable, since the source of the Magdalena River is located and such negative effects would even cause the disappearance of the source of this important water tributary for Colombia, which is the primary source of water. drinking water, energy irrigation and industrial supply for more than 50% of energy in the country. To prevent this, an eco-village will be developed in the perimeter area of the source of the Magdalena River, which does not impact the existing ecosystem, but, on the contrary, is totally friendly to the nature of the sector, preserves the ideology of the population already in turn, exercise control and care for the inhabitants of this reserved area in the municipality of San Agustín.